Dodonaea viscosa var. angustifolia Inhibits Germ Tube and Biofilm Formation by C. albicans. (9th October 2013) - Naicker, Serisha Devi; Patel, Mrudula
Abstract : The virulence factors of Candida albicans are germ tube and biofilm formation, adherence to host tissues, and production of hydrolytic enzymes. This study investigated the effect of Dodonaea viscosa var. angustifolia extract on the germ tube and biofilm formation of C. albicans . Serum containing the three subinhibitory concentrations of leaf extract was inoculated with C. albicans, incubated, and viewed under a light microscope. Number of cells with germ tube was recorded and the results were analysed using Scheffe test for pairwise comparison. Biofilms were grown on coverslips in the presence of plant extracts and processed for scanning electron microscopy (SEM). Planktonic cells were grown in the presence of plant extract for 6 h and processed for electron microscopy (TEM). The crude plant extract significantly (P < 0.01 ) reduced the germ tube formation of C. albicans at 3.125 (85.36%), 1.56 (61.91%), and 0.78 mg/mL (26.27%) showing a concentration dependent effect. SEM results showed concentration dependent reduction in biofilm and hyphae formation. TEM results showed that the plant extract caused damage to the cell wall and cell membrane. DVA extract has ability to reduce virulence of C. albicans by inhibiting germ tube and biofilm formation through damage to the cell wall. Therefore, it has therapeutic potential.